Implementation of Character Education in Madrasah Aliyah in Era 5. 0 - Elyakim Nova Supriyedi Patty; Sunardin Sunardin; Sutrisno Sutrisno; Darul Ilmi (International Journal of Educational Narratives, 2024)
Background. The 5.0 era generation is a generation that has developed knowledge of Information and Communication Technology (ICT). Some of the skills that students must have are: Productive thinking, innovative, artistic, mastery of communication and mastery of cooperation. Strengthening character education certainly needs to be realized, this aims to instill moral traits (ethical character) which makes morals an individual characteristic. Purpose. The aim of this research is to understand the outline and system for determining character education for students at Madrasah Aliyah. Apart from that, this research also aims to explain to students what character education looks like in passing through the 5.0 education era. Method. The method used is a quantitative survey model, a survey using online-based Google Form and in-depth interviews with students.    Results. The results of the research can explain that the implementation of character education is actually very important to equip students for the future. Character education is implemented with a system that utilizes information technology available in schools, so that morals can be formed and at the same time can also develop mastery of skills in the field of ICT, think productively, innovatively and can be achieved by students in the future in the 5.0 era. Conclusion. Research limitations that is, researchers cannot explain the overall implementation of character education for students at Madrasah Aliyah in depth and effectively. Researchers hope that future research can handle the implementation of character education for Madarasah Aliyah students in the 5.0 era well and more thoroughly.